DNA methylation of PTGER4 in peripheral blood plasma helps to distinguish between lung cancer, benign pulmonary nodules and chronic obstructive pulmonary disease patients - Schotten, Lea Maria; Darwiche, Kaid; Seweryn, Michal; Yildiz, Vedat; Kneuertz, Peter J.; Eberhardt, Wilfried E. E.; Eisenmann, Stephan; Welter, Stefan; Sisson, Brianna E.; Pietrzak, Maciej; Wiesweg, Marcel; Ploenes, Till; et al. (European journal of cancer, 2021)
Lung cancer screening; Methylation markers; PTGER4; SHOX2
Gesehen am 03.08.2021